The extra-nuclear interactome of the estrogen receptors: implications for physiological functions. (1st December 2021) - Acconcia, Filippo; Fiocchetti, Marco; Busonero, Claudia; Fernandez, Virginia Solar; Montalesi, Emiliano; Cipolletti, Manuela; Pallottini, Valentina; Marino, Maria
Abstract: Over the last decades, a great body of evidence has defined a novel view of the cellular mechanism of action of the steroid hormone 17β-estradiol (E2) through its estrogen receptors (i.e., ERα and ERβ). It is now clear that the E2-activated ERs work both as transcription factors and extra-nuclear plasma membrane-localized receptors. The activation of a plethora of signal transduction cascades follows the E2-dependent engagement of plasma membrane-localized ERs and is required for the coordination of gene expression, which ultimately controls the occurrence of the pleiotropic effects of E2. The definition of the molecular mechanisms by which the ERs locate at the cell surface (i.e., palmitoylation and protein association) determined the quest for understanding the specificity of the extra-nuclear E2 signaling. The use of mice models lacking the plasma membrane ERα localization unveiled that the extra-nuclear E2 signaling is operational in vivo but tissue-specific. However, the underlying molecular details for such ERs signaling diversity in the perspective of the E2 physiological functions in the different cellular contexts are still not understood. Therefore, to gain insights into the tissue specificity of the extra-nuclear E2 signaling to physiological functions, here we reviewed the known ERs extra-nuclear interactors and tried to extrapolate from available databases the ERα and ERβ extra-nuclear interactomes. Based on literature data, it is possible to conclude that by specifically binding to extra-nuclear localized proteins in different sub-cellular compartments, the ERs fine-tune their molecular activities. Moreover, we report that the context-dependent diversity of the ERs-mediated extra-nuclear E2 actions can be ascribed to the great flexibility of the physical structures of ERs and the spatial-temporal organization of the logistics of the cells (i.e., the endocytic compartments). Finally, we provide lists of proteins belonging to the potential ERα and ERβ extra-nuclear interactomes and propose that the systematic experimental definition of the ERs extra-nuclear interactomes in different tissues represents the next step for the research in the ERs field. Such characterization will be fundamental for the identification of novel druggable targets for the innovative treatment of ERs-related diseases. Highlights: History of the extra-nuclear signaling of ERs is reviewed. Experimentally identified protein interactors of the ERs are reviewed. Novel extra-nuclear-only interactors of the ERs are bioinformatically identified. The extra-nuclear ERs actions diversity is linked to their extra-nuclear interactors.